Ultrafast and highly sensitive infrared photodetectors based on two-dimensional oxyselenide crystals - Yin, Jianbo (Nat Commun, 2018)
Infrared light detection and sensing is deeply embedded in modern technology and human society and its development has always been benefitting from the discovery of various photoelectric materials. The rise of two-dimensional materials, thanks to their distinct electronic structures, extreme dimensional confinement and strong light–matter interactions, provides a material platform for next-generation infrared photodetection. Ideal infrared detectors should have fast respond, high sensitivity and air-stability, which are rare to meet at the same time in one two-dimensional material. Herein we demonstrate an infrared photodetector based on two-dimensional Bi(2)O(2)Se crystal, whose main characteristics are outstanding in the whole two-dimensional family: high sensitivity of 65 AW(−1) at 1200 nm and ultrafast photoresponse of ~1 ps at room temperature, implying an intrinsic material-limited bandwidth up to 500 GHz. Such great performance is attributed to the suitable electronic bandgap and high carrier mobility of two-dimensional oxyselenide.